Shifting Culture: A New CNO Leading to Nursing Excellence. (September 2018) - Johnston, Diann; Villa, Julie
Abstract : A new chief nursing officer describes the transformational leadership strategies she and her team used to turn their hospital, once below the national mean on National Database of Nurse Sensitive Indicators and patient/RN satisfaction scores, into a highly engaged and effective organization achieving top-performing outcomes.